The maximum amount judicial order: legal nature and practical issues (Acta Judicial Journal, 2020)
Since the so-called "maximum amount judicial order" was introduced into our legislation, it has been configured as an executive title which, although of notable utility as an instrument to facilitate the repair of damages caused as a result of the circulation of motor vehicles, does not it has stopped raising practical problems, both around its creation process and its application in civil courts. Issues that, not only did not dissipate, but were increased since the publication of the LEC 1/2000, given that it does not sympathize well with the executive system of a supposedly unitary nature established in our legislation by said procedural norm. The purpose of this paper is to systematize issues raised around this executive title and analyze it from the perspective of its legal nature in order to clarify the practical issues that it raises.
Keywords: Maximum amount judicial order, circulation of motor vehicles, practical problems, executive title